A DFT investigation of CsMgX3 (X = Cl, Br) halide perovskites: Electronic, thermoelectric and optical properties - Sharma, Ramesh; Dey, Aditya; Ahmed Dar, Sajad; Srivastava, Vipul (Computational and theoretical chemistry, 2021)
Novelty statement The CsMgX3 (X=Cl and Br) compounds are investigated with respect to their electronic, thermoelectric and optical properties using FP-LAPW method with PBE-GGA and mBJ-GGA potentials. One of the novelties in the compounds noticed that they have excellent thermoelectric efficiency measured bypower factor (PF), henceforth figure of merit (ZT). We predict PF value 2.75 x1011 and 3.98 x1011W/K2ms for CsMgCl3 and CsMgBr3, respectively at room temperature, which increases as temperature increases. Further, these materials display ZT values of 0.69 and 0.75 at room temperature, which approach to 0.97 and 0.99 at certain chemical potential for CsMgCl3 and CsMgBr3, respectively. Consequently, promising materials for thermoelectric applications. [Display omitted] •Electronic band profile exhibit wide band gap of 6.35 and 4.26 eV, in CsMgCl3 and CsMgBr3 compounds, respectively.•Remarkable figure of merit, 0.69 and 0.75 at 300 K, which approaches to 0.97 and 0.99 at certain chemical potential for CsMgCl3 and CsMgBr3, respectively.•Materials found suitable in UV region and can be employed as UV absorbers implanted in sensitive devices to protect from UV-rays.•Our work pronounces novel results and can be beneficial for the advancement in the thermoelectric applications as well. The electronic, thermoelectric and optical properties of cubic CsMgX3 (X = Cl, Br) are performed using full potential augmented plane wave (FP-LAPW) method with the generalized gradient approximation (GGA) and modified Becke-Johnson (mBJ-GGA) approximation as exchange correlation potentials. The band profile of CsMgCl3 and CsMgBr3 using mBJ-GGA potentials exhibits indirect wide energy band gap of 6.35 and 4.26 eV, respectively. Further, thermoelectric properties are carried out as a function of temperature (100–1200 K) and chemical potential using BoltzTrap code. It has been found that thermoelectric efficiency increases with increasing temperature upto 1200 K. The figure of merit (ZT) values are calculated to 0.69 and 0.75 at room temperature for CsMgCl3 and CsMgBr3, respectively. Furthermore, optical properties are computed in the energy spectrum (0–12 eV). These materials absorb light in ultra violet region and can be used as absorber of UV-rays. Also materials are suitable for thermoelectric power generator applications.